Морфометрична оцінка особливостей ремоделювання артерій товстої кишки при токсичному гепатиті - Гнатюк, М.С.; Головатюк, Л.М. (Таврический медико-биологический вестник, 2009)
В эксперименте изучены особенности ремоделирования артерий толстой кишки в

разные сроки протекания токсического гепатита. Наиболее выраженные

структурне изменения в исследуемых сосудах виявлено на 7 сутки создания

данной патологии. При этом наиболее поврежденными оказались мелкие артерии

толстой кишки, ремоделирование которых характеризовалось утолщением их

стенки, сужением просвета, повреждением эндотелиоцитов, что приводит к

ухудшению кровообращения исследуемого органа, гипоксии, дистрофии, некроза

клеток и тканей. Особенности изменений в артериях толстой кишки следует

учитывать при профилактике, диагностике и коррекции данной патологии. The remodelling of the colon arteries at various terms of duration of toxic hepatitis has

been studied in the experiment. The distinctly expressed structural changes in the

vessels investingated were observed on the seventh twenty-four hours of this

pathological formation. The smallest arteries of the colon have turned out to be the

most damaged, their remodeling has been characterized by thickening of their walls,

narrowing of lumina, damaging of endotheliocyti which inevitably leads to deterioration

of blood supply to the organ examined, to hypoxia, dystrophy and tissue necrosis. The

peculiarities of structural changes in the arteries of the intestinum crassum should be

taken into consideration by clinicists during prophylactic activities, diagnosis making

and any correction of the pathological condition in question.